Decomposition of vibration signals into deterministic and nondeterministic components and its capabilities of fault detection and identification - Barszcz, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
The paper investigates the possibility of decomposing vibration signals into deterministic and nondeterministic parts, based on the Wold theorem. A short description of the theory of adaptive filters is presented. When an adaptive filter uses the delayed version of the input signal as the reference signal, it is possible to divide the signal into a deterministic (gear and shaft related) part and a nondeterministic (noise and rolling bearings) part.
Keywords: decomposition; vibrations; deterministic component; nondeterministic component; rolling bearing